Credit cycles and macro fundamentals - Siem Jan Koopman; Roman Kräussl; André Lucas (Goethe University Frankfurt, Center for Financial Studies (CFS), 2006)
We study the relation between the credit cycle and macro economic fundamentals in an intensity based framework. Using rating transition and default data of U.S. corporates from Standard and Poor's over the period 1980-2005 we directly estimate the credit cycle from the micro rating data. We relate this cycle to the business cycle, bank lending conditions, and financial market variables. In line with earlier studies, these variables appear to explain part of the credit cycle. As our main contribution, we test for the correct dynamic specification of these models. In all cases, the hypothesis of correct dynamic specification is strongly rejected. Moreover, accounting for dynamic mis-specification, many of the variables thought to explain the credit cycle, turn out to be insignificant. The main exceptions are GDP growth, and to some extent stock returns and stock return volatilities. Their economic significance appears low, however. This raises the puzzle of what macro-economic fundamentals explain default and rating dynamics
urn:nbn:de:hebis:30-38070
Keywords: G11; G21; 330; Credit Cycles; Business Cycles; Bank Lending Conditions; Unobserved Component Models; Intensity Models; Monte Carlo Likelihood